ANALYSIS OF PT. CELEBIT CIRCUIT TECHNOLOGY'S BUSINESS NEGOTIATION STRATEGY WITH CUSTOMERS - Aulia, Shifa; Barkah, Cecep Safa’atul; Achmawati Novel, Nurilah Jamil (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
In business negotiations, there is often little way to know how the agreement will be executed properly through negotiations and agreements with both parties concerned. The existence of the company's problems with the customer, the company must be able to provide alternative solutions to problems that occur by negotiating with the customer to seek mutual agreement as decision making. Informants from the PPC (Pre Production Control) / PPIC (Plan Production Inventory Control) section made an alternative as an initial negotiation with the customer in taking the negotiation agreement that occurred. In this study the authors used qualitative methods, with data collection techniques through interviews and literature study and interview data analysis techniques were carried out such as observing, discussing and describing the problem in a certain way. Based on the results of interviews with PPC (Pre Production Control) / PPIC (Plan Production Inventory Control) officers, there are several alternative strategies such as delivery warnings, production deliveries, alternative rooms and partial deliveries. With the end of the "win-lose" negotiation, the company has to find a way out of the problem that actually all parties benefit and see long-term opportunities in the negotiations that occur.